Editorial - Alice De Marchi Pereira de Souza; Amana Mattos; Andréa Barbará da Silva Bousfield; Edna Lúcia Tinoco Ponciano; Fábio Santos Bispo; Filipe Degani-Carneiro; Jimena de Garay Hernández; Kamilly Souza do Vale; Laura Cristina de Toledo Quadros; Marcos Vinicius Brunhari; Nazaré Albuquerque Hayasida; Patrícia Lorena Quitério; et al. (Estudos e Pesquisas em Psicologia)
Alice De Marchi Pereira de Souza, Amana Mattos, Andréa Barbará da Silva Bousfield, Edna Lúcia Tinoco Ponciano, Fábio Santos Bispo, Filipe Degani-Carneiro, Jimena de Garay Hernández, Kamilly Souza do Vale, Laura Cristina de Toledo Quadros, Marcos Vinicius Brunhari, Nazaré Albuquerque Hayasida, Patrícia Lorena Quitério, Rebeca Valadão Bussinger, Rosana Lazaro Rapizo, Rodolfo Rodrigues de Souza, Sabrina Dal Ongaro Savegnago, Silvia Renata Magalhães Lordello Borba Santos, Vitor Castro Gomes